2021
DOI: 10.46328/ijonses.106
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Digital Comics in Distance Learning During COVID-19

Abstract: The aim of the study is to reveal the effect of digital comics material on students' academic success, their views on distance education, course and digital comics. In the study conducted during the 2019-2020 academic year and the pandemic, digital comics material was created in the Pixton design program for the aim of the acquisition of “different management styles in terms of basic principles of democracy," in the learning area of active citizenship in the 6th grade Social Studies curriculum. It is known tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 6 publications
3
15
0
1
Order By: Relevance
“…-Remote teaching‖ has become a worldwide phenomenon due to COVID-19, resulting in a temporary shift to online teaching (Ananga, 2020;Angelova, 2020;Atabey, 2021;Bradley, 2021;Cakin & Kulekci Akyavuz, 2021;ElSaheli-Elhage, 2021;Hodges at al., 2020;Ilhan, G. O., Kaba & Sin, 2021;Marpa, 2021;Paudel, 2021;Serhan, 2019;Unger & Meiran, 2020). These exceptional circumstances have brought the use of technology in education to the attention of a broader university public.…”
Section: Introductionmentioning
confidence: 99%
“…-Remote teaching‖ has become a worldwide phenomenon due to COVID-19, resulting in a temporary shift to online teaching (Ananga, 2020;Angelova, 2020;Atabey, 2021;Bradley, 2021;Cakin & Kulekci Akyavuz, 2021;ElSaheli-Elhage, 2021;Hodges at al., 2020;Ilhan, G. O., Kaba & Sin, 2021;Marpa, 2021;Paudel, 2021;Serhan, 2019;Unger & Meiran, 2020). These exceptional circumstances have brought the use of technology in education to the attention of a broader university public.…”
Section: Introductionmentioning
confidence: 99%
“…The latest publication in 2021 by [9] tested comics with a scientific approach and received positive responses from students. Finally, a single class experiment was conducted by [10] using digital comics for social science learning in the pandemic era. They found that digital comics influenced student learning success positively.…”
Section: Introductionmentioning
confidence: 99%
“…While the number of students enrolling in distance learning was high in the past, the COVID-19 pandemic has now caused most schools across the country to shift from classroom to distance learning with almost no time to plan (Ilhan, Kaba & Sin, 2021;Kaban, 2021;MCH Strategic Data, 2020;Niemi & Kousa, 2020;Yılmaz İnce, Kabul & Diler, 2020). Despite this widespread shift to distance learning, research on distance education is still in its early stages, and there is little research evaluating the effects of online visual arts classes for elementary, middle, and high school students.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have demonstrated the equal effectiveness of online learning platforms and face-to-face teaching (Barbour & Mulcahy, 2009;Barker & Wendel, 2001). Most research on distance education has focused on the general education population (Altowairiki, 2021;Batmang et al, 2021;Demosthenous, Panaoura & Eteokleous;Ilhan, Kaba & Sin, 2021;Kaban, 2021;Niemi & Kousa, 2020;Yılmaz İnce, Kabul & Diler, 2020;Xhelili et al, 2021). However, research on the effects of distance education in visual arts courses and the attitudes and behaviors of teachers and students in these courses is very limited (Doğru, 2020;Kaleli, 2021).…”
Section: Introductionmentioning
confidence: 99%